Comprehensive guidelines for prehabilitation in spine surgery - Paulomi Gohel; Raj Swaroop Lavadi; Mohamed-Ali H. Jawad-Makki; Rohit Prem Kumar; Ayesha Akbar Waheed; Lior M. Elkaim; Vinay Jaikumar; Nima Alan; Thomas J. Buell; Brenton Pennicooke; D. Kojo Hamilton; Nitin Agarwal (Journal of Craniovertebral Junction and Spine)
Study Design: Literature review. Objectives: Review prehabilitation techniques used for elective spine surgery to create a comprehensive list of recommendations. Methods: A systematic review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines by searching three electronic databases from 1997 to 2021. Pertinent literature reporting information on prehabilitation, applicable to spine surgery, was identified. Seventy studies were selected for further analysis. Findings from the literature were reinforced by practices employed by the authors. Results: Preoperative smoking cessation should be achieved 3–4 weeks before elective spine surgery. Preoperative weight loss programs to reach a goal BMI <35 kg/m2 may be a viable solution to minimize wound complications and surgical site infections. To minimize the negative impact of cardiopulmonary comorbidities, patients can enroll in an exercise program prior to surgery. Patients should abstain from alcohol before elective spine surgery. Patients with osteoporosis may benefit from supplementation with Vitamin D, calcium, and parathyroid hormone. Opioids should be weaned to complete cessation 6–8 weeks before surgery. Preoperative cognitive behavioral therapy (CBT) and education seem to be the most beneficial in reducing complications associated with psychiatric comorbidities. Patients should engage in a comprehensive prehabilitation regimen. Conclusion: Targeting patient risk factors with personalized interventions can improve postoperative outcomes in patients undergoing elective spine surgery.